The Death Penalty from the Perspective of Criminal Law and Islamic Law: A Comparative Study in Indonesia - Agus Alim Yusuf Alim; Nasrullah Arsyad; Sitti Ulfah (COMPENDIUM OF JUDGE MADE LAW, 2025)
Abstract: This study aims to analyze the application of the death penalty from the perspective of Indonesian criminal law and Islamic law. The study was conducted to identify common ground and principal differences between the two in upholding justice and protecting human values. The method used was normative legal research with a statutory and conceptual approach, sourced from primary, secondary, and tertiary legal sources through literature review. The results indicate that in Indonesian criminal law, the application of the death penalty is intended for crimes deemed beyond the bounds of humanity, such as drug abuse, terrorism, premeditated murder, and serious assault resulting in a cruel death. Meanwhile, in Islamic law, the death penalty (qisash) is imposed on perpetrators of intentional murder, adultery (muhshan), robbery (hirabah), rebellion (bughat), and apostasy. Islamic Sharia places the death penalty as an instrument of justice aimed at preserving life, social order, and human dignity. This study recommends that the implementation of the death penalty in Indonesia be accompanied by a clear time limit at each stage of the legal process to avoid legal uncertainty. In addition, interpretation of Islamic legal texts needs to be done contextually so that they are relevant to the development of modern legal systems and human values.